From scrolls to traditions a festschrift honoring Lawrence H. Schiffman - Miller, Stuart S. 1953-; Swartz, Michael D. 1954-; Fine, Steven 1958-; Grunhaus, Naomi 1964-; Jassen, Alex P. 1979-; Schiffman, Lawrence H. 1948- (Leiden Boston Brill, 2020)
Contents -- Preface -- A Word about Abbreviations of Journal Titles and Textual Sources -- The Publications of Lawrence H. Schiffman / Compiled by Patrick J. Angiolillo and Joshua Blachorsky with the assistance of Marlene Schiffman -- Part 1 Biblical and Second Temple Period -- Probing the Jewish Setting of Matthew 11:25-30 / Joseph L. Angel -- Demons and Dominion: Forcing Demons into the Divine Order in Jubilees and the Dead Sea Scrolls / Miryam T. Brand -- Resistance and Appropriation: The Zoroastrian Context of the Book of Tobit / David Brodsky -- The Scholasticization of Religion: From Qumran to Ctesiphon / Yaakov Elman, z'l, in collaboration with Mahnaz Moazami -- The Power of Pain: A Literary Reading of the Wicked Priest's Death(s) in 1QpHab 99 / Alexandria Frisch -- Concerning tsedaqah: Reexamining the Gospels' Teaching on Charity within the Larger World of Ancient Jewish Halakah / Jeffrey Paul García -- The Unfinished Scroll Reconsidered: 11Q19 Column 67 / Andrew D. Gross -- The Early Study of Jewish Law in the Damascus Document: Solomon Schechter and Louis Ginzberg in Conversation and Conflict / Alex P. Jassen -- The Legacy of the Flood in the Book of Jubilees / Ari Mermelstein -- Part 2 Rabbis, Other Jews, and Neighboring Cultures -- An Aramaic Power of Attorney from Ramla (1056) [T-S 13 J 114]: A Translation and Genizah Study / Ross Brann -- The Treason of Yosa Meshita (Genesis Rabba 65:27): A Rabbinic Reflection on the Fate of the Temple Lampstand / Steven Fine -- Radak's Engagement with Rabbinic Literature in His Sefer ha-Shorashim: Innovations in Light of His Predecessors' Approaches / Naomi Grunhaus -- A Tale of Two or Three Witnesses: Witness Testimony in Greco-Roman, Qumranic, and Rabbinic Court Procedure / Richard Hidary -- A Creation Sui Generis: The Evolution of a Concept / Sarra Lev -- All Law begins with Custom: Rabbinic Awareness of Popular Practice and its Implications for the Study of the Jews of Roman Palestine / Stuart S. Miller -- The Eiruv and the Outsider: A Study in Urban Conditions in Roman Palestine / Adam Mintz -- Telling Retellings: Honi the Circlemaker and the Development of Tannaitic Aggadic Discourse / Aaron D. Panken, z'l -- A New Edition of Az nefesh kol ḥai, Yannai's Qedushta for Leviticus 4:1-35 / Michael Rand -- Jacob's Image: The History of a Late Antique Motif / Alexei M. Sivertsev -- Civil and Uncivil Magic: Individual, Community, and Identity in Ancient and Medieval Jewish Curse Texts / Michael D. Swartz -- General Index.
This Festschrift in honor of Professor Lawrence H. Schiffman, a renowned authority on the Dead Sea Scrolls and Rabbinic Judaism, includes contributions by twenty of his former doctoral students, now colleagues. The volume is divided into two sections, the "Biblical and Second Temple Period" and "Rabbis, Other Jews, and Neighboring Cultures." The diverse topics covered and the wide range of interdisciplinary approaches employed reflect Professor Schiffman's success in cultivating a school of scholars who are making unique contributions to the study of the Jews and Judaism
Keywords: Jews -- Study and teaching (Higher); Judaism -- Study and teaching (Higher); Jews -- History -- 586 B.C.-70 A.D; Jews -- History -- 70-638; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Judaism -- History -- Talmudic period, 10-425; Rabbinical literature -- History and criticism; Festschrift